Czech Version of the Patient Dignity Inventory: Translation and Validation in Incurable Patients - Kisvetrová, Helena; Školoudík, David; Danielová, Libuše; Langová, Kateřina; Váverková, Renáta; Bretšnajdrová, Milena; Yamada, Yukari (Journal of pain and symptom management, 2018)
CONTEXT: The Patient Dignity Inventory (PDI) is a valid, reliable screening tool to assess a range of issues that have been reported to affect the sense of dignity in patients with life-limiting conditions. OBJECTIVES: We investigated the item characteristics, factor structure, and reliability of the Czech version of the PDI (PDI-CZ) among cancer and noncancer patients. METHODS: The PDI was translated into the Czech language following state-of-the-art criteria (a five-stage proceeding method for the translation). Two hundred thirty-nine participants completed the study (136 cancer and 103 noncancer patients). Internal consistency, test-retest reliability, and factor analysis were used for validation of the PDI-CZ. RESULTS: A Czech version of the PDI was obtained. The Cronbach's α for PDI-CZ was 0.92. Item 22 (not feeling supported by my health care providers) did not correlate with any other items, and it was skipped for factor analysis processing for this reason. Factor analysis resulted in a four-factor solution, accounting for 56.34% of the overall variance (factor loadings range, 0.37-0.92). The factor labels were as follows: loss of purpose of life; loss of autonomy; loss of confidence; and loss of social support (internal consistencies range, Cronbach's α 0.58-0.90). Test-retest reliability was assessed with 25 patients after two weeks. The resulting range of the Gwet's coefficient, AC1, was between 0.58 and 1.00. CONCLUSION: The results from the study support the reliability of the PDI-CZ and its future use in patients with incurable cancer and noncancer patients.
Keywords: dospělí; Female; kritický stav; Adult; ženské pohlaví; Neoplasms; nádory; Reproducibility of Results; lidé; Aged, 80 and over; faktorová analýza statistická; uznání; reprodukovatelnost výsledků; Male; Aged; překládání; Translating; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Factor Analysis, Statistical; Middle Aged; Respect; Critical Illness; Humans